IMPLEMENTASI KEBIJAKAN KESEJAHTERAAN SOSIAL OLEH PEMERINTAH KOTA PEKANBARU KHUSUS GELANDANGAN DAN PENGEMIS TAHUN 2024 - Putra, Armanda; Zebua, Ben Hansel Notatema (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2026)
The City of Pekanbaru faces problems related to homeless people and beggars who are spread across strategic locations. This study analyzes the implementation of Regional Regulation Number 3 of 2023 concerning the Administration of Social Welfare using a qualitative descriptive approach. The programs implemented include social rehabilitation (181 people), social security (181 people), social empowerment (201 people), and social protection (113 people). The results show that the Regional Regulation provides a comprehensive legal framework, with the Regional House of Representatives and the Social Service acting as the main implementing institutions. However, its effectiveness is limited due to budget constraints, weak coordination, and a high rate of recidivism. Increasing budget allocation and strengthening cross-sector coordination are required to achieve sustainable social transformation. Keywords: Regional Regulation, Welfare, Homeless People, Beggars.